1999
DOI: 10.1067/msy.1999.99168
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases signal inhibition of apoptosis in lipopolysaccharide-stimulated neutrophils

Abstract: These data demonstrate opposing roles of MAPKs in mediating PMN apoptosis after LPS stimulation. We conclude that LPS signal transduction by ERK inhibits PMN apoptosis while activation of p38 promotes apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Phospho‐p44/42 MAPK was not detectable in adherent vascular neutrophils (data not shown). Moreover, in accord with previous studies in human peripheral blood neutrophils (Nolan et al, 1999), SAPK/JNK was not observed in lung neutrophils from either control or endotoxin treated rats (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…Phospho‐p44/42 MAPK was not detectable in adherent vascular neutrophils (data not shown). Moreover, in accord with previous studies in human peripheral blood neutrophils (Nolan et al, 1999), SAPK/JNK was not observed in lung neutrophils from either control or endotoxin treated rats (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…Intracellular signalling via the PI3-K/Akt pathway plays an important role in regulating many cellular processes, especially granulocyte migration, activation and survival [131133]. Similarly, the ERK 1/2 pathway represents a point of convergence for multiple signaling events thereby regulating important cellular functions and fate of human neutrophils [127,134,135]. RvE1-CMKLR1 interactions initiate the activation of PI3-K resulting in phosphorylation of Akt and ribosomal S6 protein via mTOR signalling [102].…”
Section: Intracellular Signaling Mechanisms For Resolvinsmentioning
confidence: 99%
“…In addition, we found that SPP increased the amount of phosphorylated active ERK, but pharmacological inhibition of this kinase did not significantly affect neutrophil apoptosis, which shows that, in contrast to p38 MAPK, ERK is not involved in mediating the effect of SPP on spontaneous or anti-Fas-induced apoptosis. This also indicates that the signalling pathway utilized by SPP differs from those of LPS and calcium pyrophosphate dihydrate, both of which have been reported to modulate neutrophil apoptosis through activation of ERK [55,56].…”
Section: Discussionmentioning
confidence: 88%